Cash Flow Risk Management Pratices dan Sustainable Financial Performance Pada Industri Perbankan Di Indonesia - Sparta (Jurnal Liabilitas, 2022)
This study aims to see the extent to which risk management practices in companies, especially banking, influence the sustainability of conventional banking financial performance on the Indonesia Stock Exchange. The research sample is the banking industry on the IDX capital market during the period 2017 to 2019. Of the 41 banks that went public, 38 conventional banks were used as research samples. The dependent variable used is the Sustainable growth rate as a proxy for sustainable financing performance The independent variables used are Cash flow operating to total liability as a proxy for risk management practice in cash flow operating, cash flow investing to total liability, cash flow financing to total liability and cash flow operating to shareholder equity. The results show that risk management practices in cash flow finance to total libility, risk management practices in cash flow investing to total liability, risk management practices in cash flow operating to total share holder equity have an impact on the sustainability of banking financial performance. These results have implications for banking management, especially in terms of predicting the sustainability of banking financial performance. Key Words: sustainable financing performance, cash flow risk management pratices